Innovative sound transmission system for an intuitive service. Issue 23 (1st November 2013) - Kim, S.E.; Kang, T.W.; Hwang, J.H.; Kang, S.W.; Park, K.H.; Sohn, S.W.
Abstract : An innovative sound transmission system for an intuitive service utilises the human body as a sound transmission medium. By using the human body as a transmission medium, sound generation in the body and sound transmission through the body can be achieved at the same time. Sound generation in the body is based on the nonlinear characteristics of the human body. Two ultrasonic waves with different frequencies produce an audio signal at the difference frequency of the two waves during the propagation process due to the nonlinearity of the body. By substituting a transmission line with the human body, wireless sound transmission is achieved. This system does not require sound transmitters and the sound transmission line required in the conventional earphones. Users can hear sound without sound transmitters and a transmission line by touching the system without making any other noise outside.